2017
DOI: 10.1093/scan/nsx019
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and moral emotions in post-apartheid South Africa: an fMRI investigation

Abstract: Moral emotions elicited in response to others’ suffering are mediated by empathy and affect how we respond to their pain. South Africa provides a unique opportunity to study group processes given its racially divided past. The present study seeks insights into aspects of the moral brain by investigating behavioral and functional MRI responses of White and Black South Africans who lived through apartheid to in- and out-group physical and social pain. Whereas the physical pain task featured faces expressing dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 70 publications
4
25
0
Order By: Relevance
“…For example, when Asian and White participants viewed photographs of members of both racial groups in negative contexts (e.g., illness, grief, injury) and positive contexts (e.g., party, amusement, smiling), participant self-report data indicated greater perspective taking and empathy for own-race members than other-race members, particularly in the negative contexts [36]. Furthermore, several neuroimaging studies, including our own, demonstrated stronger hemodynamic activation in response to others' pain for racial ingroups versus outgroups in regions associated with mentalizing, including the medial prefrontal cortex (MPFC), temporoparietal junction (TPJ), and precuneus [12,58,63]. In our study, we concluded that, because these areas form part of networks implicated in self-referential processing, episodic memory retrieval, and thinking about other minds, heightened activity may allow for a richer representation of another's physical/psychological pain.…”
Section: Group Membership and Perspective Takingmentioning
confidence: 68%
See 2 more Smart Citations
“…For example, when Asian and White participants viewed photographs of members of both racial groups in negative contexts (e.g., illness, grief, injury) and positive contexts (e.g., party, amusement, smiling), participant self-report data indicated greater perspective taking and empathy for own-race members than other-race members, particularly in the negative contexts [36]. Furthermore, several neuroimaging studies, including our own, demonstrated stronger hemodynamic activation in response to others' pain for racial ingroups versus outgroups in regions associated with mentalizing, including the medial prefrontal cortex (MPFC), temporoparietal junction (TPJ), and precuneus [12,58,63]. In our study, we concluded that, because these areas form part of networks implicated in self-referential processing, episodic memory retrieval, and thinking about other minds, heightened activity may allow for a richer representation of another's physical/psychological pain.…”
Section: Group Membership and Perspective Takingmentioning
confidence: 68%
“…For example, in a functional magnetic resonance imaging (fMRI) study of intergroup empathy, higher EMS scores in White participants were associated with dampened neural empathic responses toward Black individuals in both physical and emotional distress [58]. And in another study, higher IMS scores in White participants were positively associated with prosocial helping behavior toward a Black individual in distress, whereas higher EMS scores were negatively associated with prosocial helping toward that individual [89].…”
Section: A Second Factor Central To Intergroup Dynamics Concerns the mentioning
confidence: 99%
See 1 more Smart Citation
“…Notable exceptions include a recent fMRI study in which, compared with White participants, Asian and Black participants with and without major depression showed enhanced amygdala activity in response to viewing White faces that displayed a range of sad expressions . In addition, a series of studies in Chinese participants have confirmed differences in empathic responses and neural activity to pain in other‐race individuals, and a recent fMRI study found differences in functional brain activity in response to in‐group and out‐group physical and social pain in White and Black South Africans who lived through apartheid . More studies with ethnically and racially diverse samples are needed to better understand the neurobiology of cognitive, affective, and social processes across groups.…”
Section: Race and Ethnicitymentioning
confidence: 99%
“…16 In addition, a series of studies in Chinese participants have confirmed differences in empathic responses and neural activity to pain in other-race individuals, [17][18][19][20][21][22] and a recent fMRI study found differences in functional brain activity in response to in-group and out-group physical and social pain in White and Black South Africans who lived through apartheid. 23 More studies with ethnically and racially diverse samples are needed to better understand the neurobiology of cognitive, affective, and social processes across groups.…”
Section: Racial Biasesmentioning
confidence: 99%